1998
DOI: 10.1136/jcp.51.8.583
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of expressions of transforming growth factor and epidermal growth factor receptor in squamous cell lesions of the urinary bladder

Abstract: Aim-To investigate the patterns of expression of transforming growth factor (TGF-) and epidermal growth factor receptor (EGFR) in squamous metaplasia and squamous cell carcinomas of the urinary bladder with and without schistosomiasis. Methods-Immunohistochemical study of the expression of TGF-and EGFR in squamous metaplasias (n = 12) and various grades of squamous cell carcinomas (n = 21) of the bladder with and without schistosomiasis. Results-Focal cytoplasmic and membranous positivity for EGFR and TGF-was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…previous report[27], a similar pattern was observed for overexpression of TGF-a in SCC (72.1%) compared to TCC (28.8%). It is possible that cases with the SCC component are more genetically unstable and had alterations not present in TCC cases.…”
supporting
confidence: 88%
“…previous report[27], a similar pattern was observed for overexpression of TGF-a in SCC (72.1%) compared to TCC (28.8%). It is possible that cases with the SCC component are more genetically unstable and had alterations not present in TCC cases.…”
supporting
confidence: 88%
“…Another important confounding factor that had been reported to increase the TGF-α expression is the presence of urinary infection (Tungekar and Linehan, 1998). In our studies this was evaluated as a categorical variable measuring the presence of leukocytes in urine by a semiquantitative technique.…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact pathophysiology underlying the transformation from keratinizing squamous metaplasia to squamous cell carcinoma is unknown, several etiologic factors have been linked its development (1,15). Chronic inflammation caused by indwelling catheters and stones, as well as infection secondary to parasites, are considered to be the most likely etiologic agents (1,3,4,8,12,13).…”
Section: Discussionmentioning
confidence: 99%
“…However, because of limited data on these types of protocols, no approach can be considered superior (1,2,10), and some have been proven ineffective (1,6,7). Most recently, some authors have suggested that EGFR could potentially be used as logic therapeutic target for keratinizing squamous metaplasia, among other bladder lesions, that are difficult to manage clinically (4,15). However, some investigators advocate for a more aggressive management with radical bladder resection to avoid development of malignant transformation (1,3,(5)(6)(7).…”
Section: Discussionmentioning
confidence: 99%